Effectiveness of the use of therapeutic bandage method in the third molar surgery: a randomized, controlled, single-blind, split-mouth (Research, Society and Development, 2022)
Objective: Extraction of semi-impacted or impacted, lower, third molars is one of the most performed procedures in the maxillofacial surgery, and inherent to it, there may be post-operative inflammatory response. Among the most common factors related to this response, pain, swelling, and trismus are the main ones. In this sense, therapeutic bandage has been used in the post-operative physiotherapy for several specialties so that muscular functions can be fully resumed and swelling, muscle spasms and pain reduced. Materials and Methods: The randomized, split-mouth, clinical trial was to assess 20 post-operative patients who underwent extraction of lower third molars with therapeutic bandage. Seven days after the extraction, swelling and trismus were the variables evaluated and pain was assessed according to the visual analogue scale (VAS). The Student’s t-test was used for comparison at significance level of 5% (α = 0.05). Results: With the results found, it was not possible to state that the therapeutic bandage protocol used in this study, given the evaluated signs and symptoms, were favorable, even providing greater comfort to patients. Conclusion: Therefore, we suggest that further studies should be performed in order to develop a protocol for application of therapeutic bandage for stomatognathic system. Clinicaltrials.gov NCT03393533. 12/05/2017 retrospectively registered.